Solid waste management plan of pharmacy faculty in Karachi university - Usmani, Mursaleen; Wahab, Abdul; Sultana, Hafsa (International Journal of Scientific World, 2014)
Solid waste is considered as a biggest pollution problem in Pakistan. Improper management of solid waste creates many problems in Pakistan like health problems by causing different disease; create unpleasant smell, land pollution and also effect the beauty of the country. The country spends lot of income for the management of solid waste. The aim of this research is to identify that solid waste is consider as an economic burden or an economic assets. For this research work, we choose the pharmacy faculty found in university of Karachi, Pakistan. We collect different type of data related with solid waste from the members of the faculty and the result of the project shows that our little effort can make lower this burden and we can convert this economic burden into economic assets. Keywords: Segregation, Bring System, Composting, Questionnaires, Dumping Site.